A Literary Crossroads: Colonial Anxiety and Ecological Imperialism in The Tale of Saidjah and Adinda - Edward Owen Teggin; Kristiawan Indriyanto (Journal of Language and Literature, 2024)
This article examines the concepts of ecological anxiety and imperialism through the prism of colonial literature, with the aim of contextualising them alongside the broader theory of colonial anxiety. The study examines The Tale of Saidjah and Adinda, contained in Max Havelaar, as a case study. The text was investigated in order to identify key signifiers of anxiety, with the buffalo being the strongest signifier identified for discussion. The premise is that colonial and ecological signifiers can be seen in the narrative containing the buffalo due to the exploitative imperial process at work and the anxiety experienced by characters such as Saidjah and Adinda when buffalo were stolen. This approach is well suited to the current study due to the way in which Multatuli has used the buffalo, both symbolically and as a major part of the narrative, to demonstrate the damage done to the Javanese people and the environment by the colonial-imperial process. This study demonstrates that colonial and ecological anxiety are closely allied fields that can be used to expand on literary works and analyses dealing with the colonial-imperial era. So too, it is argued, that Indonesia has a key role to play in future debates of both colonial and ecological anxiety.